2019
DOI: 10.1016/j.jacbts.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Hmgb1

Abstract: Corresponding Author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…It was shown that cytosolic HMGB1 binding TLR9 improves tissue repair, increased wound healing, and angiogenesis [ 88 ]. Raucci and colleagues [ 89 ] showed that protective or harmful effects of HMGB1 and TLR9 might finally dependent on the concentration of HMGB1. Hence, future studies are required to understand the detailed interaction of DNA-binding proteins to cfDNA and their impact on the resulting immunological function after tissue injury.…”
Section: Immune Sensing Of Cfdnamentioning
confidence: 99%
“…It was shown that cytosolic HMGB1 binding TLR9 improves tissue repair, increased wound healing, and angiogenesis [ 88 ]. Raucci and colleagues [ 89 ] showed that protective or harmful effects of HMGB1 and TLR9 might finally dependent on the concentration of HMGB1. Hence, future studies are required to understand the detailed interaction of DNA-binding proteins to cfDNA and their impact on the resulting immunological function after tissue injury.…”
Section: Immune Sensing Of Cfdnamentioning
confidence: 99%